De novo microdeletions and point mutations affecting SOX2 in three individuals with intellectual disability but without major eye malformations. Issue 2 (14th November 2016) - Dennert, Nicola; Engels, Hartmut; Cremer, Kirsten; Becker, Jessica; Wohlleber, Eva; Albrecht, Beate; Ehret, Julia K.; Lüdecke, Hermann‐Josef; Suri, Mohnish; Carignani, Giulia; Renieri, Alessandra; Kukuk, Guido M.; et al.
Abstract : Loss‐of‐function mutations and deletions of the SOX2 gene are known to cause uni‐ and bilateral anophthalmia and microphthalmia as well as related disorders such as anophthalmia‐esophageal‐genital syndrome. Thus, anophthalmia/microphthalmia is the primary indication for targeted, "phenotype first" analyses of SOX2 . However, SOX2 mutations are also associated with a wide range of non‐ocular abnormalities, such as postnatal growth retardation, structural brain anomalies, hypogenitalism, and developmental delay. The present report describes three patients without anophthalmia/microphthalmia and loss‐of‐function mutations or microdeletions of SOX2 who had been investigated in a "genotype first" manner due to intellectual disability/developmental delay using whole exome sequencing or chromosomal microarray analyses. This result prompted us to perform SOX2 Sanger sequencing in 192 developmental delay/intellectual disability patients without anophthalmia or microphthalmia. No additional SOX2 loss‐of‐function mutations were detected in this cohort, showing that SOX2 is clearly not a major cause of intellectual disability without anophthalmia/microphthalmia. In our three patients and four further, reported "genotype first" SOX2 microdeletion patients, anophthalmia/microphthalmia was present in less than half of the patients. Thus, SOX2 is another example of a gene whose clinical spectrum is broadened by the generation of "genotype first" findings using hypothesis‐free, genome‐wide methods. © 2016 Wiley Periodicals, Inc.